2017
DOI: 10.1021/acs.oprd.7b00197
|View full text |Cite
|
Sign up to set email alerts
|

General Principles and Strategies for Salting-Out Informed by the Hofmeister Series

Abstract: Overarching principles for salting-out extraction are long-established but poorly disseminated. We highlight the opportunity for more widespread application of this technique using the Hofmeister series as a foundational basis for choosing the right salt. The power of this approach is exemplified by the aqueous workup of a highly water-soluble nucleoside in which the use of sodium sulfate allowed for high recoveries without relying on back extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
256
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(289 citation statements)
references
References 194 publications
7
256
2
2
Order By: Relevance
“…The Hofmeister anions series SCN – < I – < NO 3 – < Br – < Cl – are well‐known due to their potency of solubilizing protein, in which the salting‐out anions like Cl – are responsible for reducing the proteins solubility, and the salting‐in anions like Br – or I – increase the proteins solubility , . The salting‐out or salting‐in effect of anions also exist in the surfactant micellar system, which is critical for the micellization, dictating the micellar shape .…”
Section: Discussionmentioning
confidence: 99%
“…The Hofmeister anions series SCN – < I – < NO 3 – < Br – < Cl – are well‐known due to their potency of solubilizing protein, in which the salting‐out anions like Cl – are responsible for reducing the proteins solubility, and the salting‐in anions like Br – or I – increase the proteins solubility , . The salting‐out or salting‐in effect of anions also exist in the surfactant micellar system, which is critical for the micellization, dictating the micellar shape .…”
Section: Discussionmentioning
confidence: 99%
“…We were wary of carrying out an aqueous work‐up because we had previously found that the enal is partially water soluble and required multiple extractions even from brine solutions, resulting in excessively large volumes of solvent. However, a recent report highlighting the beneficial effects of using Na 2 SO 4 to salt‐out water soluble compounds prompted us to reinvestigate aqueous work‐ups . Using this strategy, just two extractions enabled full recovery of enal 1 , which was purified by column chromatography; it was essential to pre‐treat the silica gel with water (50 wt %) to ensure efficient removal of any remaining succinaldehyde and oligomeric material during chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…Die Fähigkeit dieser Kationen, Proteine auszufällen, hängt von ihrer Ladungsdichte ab. Diese führt zu Ordnungseffekten des Lösungsmittels Wasser, was zu einer Erhöhung des hydrophoben Effektes sowie zur Proteinaggregation und ‐fällung führt . Betrachtet man die Auswirkungen von POMs auf die Lösungsstabilität von Makromolekülen, ist die große Hydrathülle der POMs, ihre große Polarisierbarkeit und niedrige Ladungsdichte zu beachten .…”
Section: Einleitung: Grundlagen Der Pom‐kation‐wechselwirkungenunclassified